Combined liver–cytokine humanization comes to the rescue of circulating human red blood cells - Song, Yuanbin; Shan, Liang; Gbyli, Rana; Liu, Wei; Strowig, Till; Patel, Amisha; Fu, Xiaoying; Wang, Xiaman; Xu, Mina L.; Gao, Yimeng; Qin, Ashley; Bruscia, Emanuela M.; et al. (Science (American Association for the Advancement of Science), 2021)
The study of primary human red blood cell (huRBC) disorders such as sickle cell disease (SCD) and infectious diseases such as malaria has been hampered by a lack of in vivo models of human erythropoiesis. Song et al. transferred human fetal liver cells into MISTRG mice, which are immunodeficient and are genetically engineered with several human genes involved in hematopoiesis. This approach was unsuccessful because mature huRBCs are rapidly destroyed in the mouse liver. They then used CRISPR-Cas9 to mutate these mice into a fumarylacetoacetate hydrolase–deficient strain, allowing them to replace the mouse liver with engrafted human hepatocytes. These mice exhibited enhanced human erythropoiesis and circulating huRBC survival and could recapitulate SCD pathology when reconstituted with SCD-derived HSCs. Science , this issue p. 1019 Liver- and cytokine-humanized immunodeficient mice can effectively model human red blood cell disorders. In vivo models that recapitulate human erythropoiesis with persistence of circulating red blood cells (RBCs) have remained elusive. We report an immunodeficient murine model in which combined human liver and cytokine humanization confer enhanced human erythropoiesis and RBC survival in the circulation. We deleted the fumarylacetoacetate hydrolase ( Fah ) gene in MISTRG mice expressing several human cytokines in place of their murine counterparts. Liver humanization by intrasplenic injection of human hepatocytes (huHep) eliminated murine complement C3 and reduced murine Kupffer cell density. Engraftment of human sickle cell disease (SCD)–derived hematopoietic stem cells in huHepMISTRG Fah −/− mice resulted in vaso-occlusion that replicated acute SCD pathology. Combined liver–cytokine–humanized mice will facilitate the study of diseases afflicting RBCs, including bone marrow failure, hemoglobinopathies, and malaria, and also preclinical testing of therapies.